국가 기후위기적응정보 표준분류체계 개발(Ⅰ): 기본구조와 활용방안 - 서도현(Seo, Do Hyun); 오윤영(Oh, Yunyeong); 이은정(Lee, Eun Jeong); 진형아(Jin, Hyungah); 전성우(Jeon, Seong Woo); 김지연(Kim, JiYeon); 노순아(Roh, Soon-A); 백지원(Baek, Jiwon); 임철수(Lim, CheolSoo); 유명수(Yoo, Myungsoo) (한국기후변화학회지, 2023)
In recent years, the global climate crisis has triggered a surge in extreme climate events, necessitating comprehensive responses beyond greenhouse gas reduction, including robust adaptation strategies. South Korea, is also grappling with an increasing demand for climate crisis adaptation information as a critical asset for shaping effective response measures. Despite substantial data generation by various governmental agencies, the practical utilization of adaptation information on the National/Local Adaptation Measures remains challenging due to a lack of consistent standards and data complexity. To address this issue, this study proposes the Korea Climate Crisis Adaptation Information Taxonomy(KAD-Taxonomy). This structured system classifies adaptation information into 3 primary categories: science-based data, adaptation solutions, and policy evaluations, further connected to 8 intermediate sectors and Climate Scenarios(RCP/SSP). The KAD-Taxonomy features an interactive, two-way(top down and bottom up) connection structure and incorporates a systematic classification coding plan based on the 72 national climate risks selected in "The 3rd enhancement of the National Climate Adaptation Plan" in South Korea. This systemic link is designed to provide information on current damage assessments and future prospects together matching of the Climate Impact Drivers(CIDs). The KAD-Taxonomy will serve as the key structure for adaptive information management and linkage system for a comprehensive climate crisis adaptation information platform, which investigates and evaluates climate impacts and ripple effects across all sectors. Finally, its enhancement will be an ongoing process through the collaborative efforts of the National Climate Crisis Adaptation Research Consultative Body, comprising 10 research institutes dedicated to adaptation information production. KCI Citation Count: 0